2015
DOI: 10.1002/cbic.201500343
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Hydrophobic Pocket and Helix 11 in Determining the Modes of Action of Prenylated Flavonoids and Isoflavonoids in the Human Estrogen Receptor

Abstract: Six prenylated (iso)flavonoids were purified from a licorice root extract and subjected to competition experiments with six commercially available (iso)flavonoids. The agonistic and antagonistic activities of these compounds towards both hERα (human estrogen receptor alpha) and hERβ were determined. Differences in the modes of action (agonist or antagonist) were observed for the various compounds tested. In general, each compound had the same mode of action towards both ERs. In silico modeling was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…Prenylated isoflavonoids (glabrene, 3′-hydroxy-4′- O -methyl-glabridin, 4′- O -methyl-glabridin, hispaglabridin A, hispaglabridin B, glyceofuran, glyceollidin II, glyceollin I, glyceollin II, glyceollin III, glyceollin IV, glyceollin V, dehydroglyceollidin II, dehydroglyceollin I, dehydroglyceollin II, dehydroglyceollin, III, dehydroglyceollin IV) and one prenylated flavone (glabrol) were previously purified and chemically characterized 22 , 23 . Wighteone, lupiwighteone, luteone, 2,3-dehydrokievitone, licoisoflavone A, neobavaisoflavone, iso-osajin and 6,8-diprenygenistein were purchased from Plantech UK (Reading, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Prenylated isoflavonoids (glabrene, 3′-hydroxy-4′- O -methyl-glabridin, 4′- O -methyl-glabridin, hispaglabridin A, hispaglabridin B, glyceofuran, glyceollidin II, glyceollin I, glyceollin II, glyceollin III, glyceollin IV, glyceollin V, dehydroglyceollidin II, dehydroglyceollin I, dehydroglyceollin II, dehydroglyceollin, III, dehydroglyceollin IV) and one prenylated flavone (glabrol) were previously purified and chemically characterized 22 , 23 . Wighteone, lupiwighteone, luteone, 2,3-dehydrokievitone, licoisoflavone A, neobavaisoflavone, iso-osajin and 6,8-diprenygenistein were purchased from Plantech UK (Reading, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Prenylated isoflavonoids (glabrene, 3′-hydroxy-4′- O -methyl-glabridin, 4′- O -methyl-glabridin, hispaglabridin A, hispaglabridin B, glyceofuran, glyceollidin II, glyceollin I, glyceollin II, glyceollin III, glyceollin IV, glyceollin V, dehydroglyceollidin II, dehydroglyceollin I, dehydroglyceollin II, dehydroglyceollin, III, dehydroglyceollin IV) and one prenylated flavone (glabrol) were previously purified and chemically characterized 45 , 46 . 6-Prenylnaringenin, propidium iodine (PI), Phe-Arg β-naphthylamide dihydrochloride (PaβN), ampicillin and ciprofloxacin were purchased from Sigma Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, no evidence was found for any estrogen antagonist action by 8-PN at concentrations of up to 10 −6 M [ 62 ]. Likewise, results from a yeast-based estrogen bioassay indicated a purely agonistic action at both ER subtypes [ 69 ]. In silico modeling of ER binding further suggested that chain prenylation without an increase in molecular length, which enables 8-PN to fit into the hydrophobic pocket in the human ER, is responsible for the high agonist activity of 8-PN compared with naringenin [ 69 ].…”
Section: Estrogenic Activity Of 8-pnmentioning
confidence: 99%